2020
DOI: 10.1038/s41598-020-74746-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced EGFR and increased miR-221 is associated with increased resistance to temozolomide and radiotherapy in glioblastoma

Abstract: Despite aggressive treatment with temozolomide and radiotherapy and extensive research into alternative therapies there has been little improvement in Glioblastoma patient survival. Median survival time remains between 12 and 15 months mainly due to treatment resistance and tumor recurrence. In this study, we aimed to explore the underlying mechanisms behind treatment resistance and the lack of success with anti-EGFR therapy in the clinic. After generating a number of treatment resistant Glioblastoma cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
4
6
0
Order By: Relevance
“…Among the 42 genes (Supplementary Table 6), we identified several genes involved in the TMZ response that are worth mentioning. The EGFR gene, which showed a significant downregulation in Non-Resp samples, is consistent with literature data showing that glioblastoma TMZ-resistant cell lines lack EGFR activation and expression (30). Our results are, as well, confirmed for the upregulation of the CA9 gene in the Non-Resp group, the inhibition of which enhances the sensitivity of glioma cells to TMZ treatment, and highlights the value of developing small molecules or antibodies against the CA9 pathway, for combination therapy with TMZ (31) (Supplementary Table 9; Figure 5A).…”
Section: Whole Transcriptome Analysis (Wta)supporting
confidence: 91%
“…Among the 42 genes (Supplementary Table 6), we identified several genes involved in the TMZ response that are worth mentioning. The EGFR gene, which showed a significant downregulation in Non-Resp samples, is consistent with literature data showing that glioblastoma TMZ-resistant cell lines lack EGFR activation and expression (30). Our results are, as well, confirmed for the upregulation of the CA9 gene in the Non-Resp group, the inhibition of which enhances the sensitivity of glioma cells to TMZ treatment, and highlights the value of developing small molecules or antibodies against the CA9 pathway, for combination therapy with TMZ (31) (Supplementary Table 9; Figure 5A).…”
Section: Whole Transcriptome Analysis (Wta)supporting
confidence: 91%
“…Among the 42 genes (Table 6S), we identified several genes involved in the TMZ response that are worth mentioning. The EGFR gene, which showed a significant downregulation in Non-Resp samples, is consistent with literature data showing that glioblastoma TMZ-resistant cell lines lack EGFR activation and expression 30 . Our results are, as well, confirmed for the upregulation of the CA9 gene in the Non-Resp group, the inhibition of which enhances the sensitivity of glioma cells to TMZ treatment, and highlights the value of developing small molecules or antibodies against the CA9 pathway, for combination therapy with TMZ 31 (Table 9S, Fig 5a).…”
Section: Resultssupporting
confidence: 91%
“…The present study found a lowered expression of EGFR in drugresistant, quiescent CSCs derived from TMZ-R tumors. Our findings corroborate EGFR expression and activity patterns observed in several TMZ-resistant cell lines and GBM patient tumor tissues [51]. For example, Areeb et al report that in addition to deficient EGFR expression in treatment-resistant cells, there is significant upregulation of the EGFR-targeting miR-221, which likely serves as a mechanism of reduced EGFR expression.…”
Section: Discussionsupporting
confidence: 88%